Perkembangan Moral Kohlberg Menurut Perspektif Islam - Asfiyah, Wardatul (STAI Bumi Silampari, 2023)
In the world of society, we cannot be separated from certain laws, rules relating to one of them are morals, a moral person will understand what behavior he must leave is so that he will develop in a better direction. As with growth, development also has different stages. In this paper, the authors use the type of research library research. As a result, Kohlberg concluded that the way people perseivemoral issues is a reflection of cognitive development. Lawrence Kohlberg, emphasized that moral development primarily involves moral reasoning and take place in stages, namely the pre-convention, convention, and post convention level. Meanwhile, islam gives clear indications that the influence of the family environment is enormous, although within limits it can replace educated nature. Parents and the environment that affect a child. It is the parents who will lead the child to become a good person and it is the parents who are the first scaffolding who can see and correct the child’s development, be it emotional, social and moral development. Therefore, to instill good moral development, the Prophet suggested that this moral development be carried out as early as possible.